Does Sustainability Pay? Evidence from the Food Sector. Issue 3 (4th May 2019) - Acar, Mehmet Fatih; Aktas, Emel; Agan, Yavuz; Bourlakis, Michael
ABSTRACT: This research investigates sustainability concepts, linking them with social, environmental, and operational activities in the food supply chain. Building on the literature treating social sustainability as an antecedent of environmental sustainability, we present the effects of environmental sustainability on operational performance using constructs that reflect flexibility, quality, and responsiveness. For this purpose, manufacturing companies in the Turkish food industry are surveyed and 101 responses are collected. A partial least squares structural equation model (PLS-SEM) is constructed to test the reliability and the validity of the measurement model and the structural model. The results show that social sustainability is positively associated with environmental sustainability. Moreover, environmental sustainability has a positive influence on operational performance measures: flexibility, quality, and responsiveness with effect sizes that range from medium to large. Organizations in the food supply chain should consider not only the economic, but also the social and the environmental aspects of sustainability. To do this, governments could inform manufacturers in the food sector about the importance of sustainability and encourage them with different incentives towards more sustainable operational practices. This work establishes that investing in social and environmental sustainability returns increased operational performance. The limitation of the research is the size of the sample. In the future, the questionnaire can be used to compare results from other countries and other sectors.